The role of social capital in the task force for preventing and handling sexual violence on campus - Zarkasi, Irwa Rochimah; Karolina, Cut Meutia (Informasi, 2024)
Higher education institutions are required to establish a Task Force for the Prevention and Handling of Sexual Violence (PPKS). The presence of the PPKS Task Force within the campus requires thorough preparation so that its existence can be accepted and beneficial. Therefore, this research aims to examine how social capital is utilized by PPKS Task Force to strengthen its presence. The concept of social capital in organizational management is used for analysis. Using a qualitative approach, data collection was conducted through interviews with the chairperson and members of PPKS Task Force in three campuses where the PPKS Task Force has been established for more than 6 months. The research findings indicate the existence of bonding social capital through the reinforcement of vision, mission, and shared perceptions among Task Force members, which serves as an initial step before engaging in other activities. Additionally, there is bridging social capital through trust and support from the campus's internal stakeholders and related parties directly associated with the campus. Another crucial aspect is linking social capital through collaboration with external parties and various entities capable of providing support for PPKS Task Force activities and tasks.